Large population cell characterization using quantitative phase cytometer. Issue 5 (26th April 2017) - Jin, Di; Sung, Yongjin; Lue, Niyom; Kim, Yang‐Hyo; So, Peter T. C.; Yaqoob, Zahid
Abstract: A major challenge in cellular analysis is the phenotypic characterization of large cell populations within a short period of time. Among various parameters for cell characterization, the cell dry mass is often used to describe cell size but is difficult to be measured directly with traditional techniques. Here, we propose an interferometric approach based on line‐focused beam illumination for high‐content precision dry mass measurements of adherent cells in a non‐invasive fashion—we call it quantitative phase cytometry (QPC). Besides dry mass, abundant cellular morphological features such as projected area, sphericity, and phase skewness can be readily extracted from the QPC interferometric data. To validate the utility of our technique, we demonstrate characterizing a large population of ∼ 10 4 HeLa cells. Our reported QPC system is envisioned as a promising quantitative tool for label‐free characterization of a large cell count at single cell resolution. © 2017 International Society for Advancement of Cytometry